1983
DOI: 10.1007/bf00541592
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drugs on serum histidine levels in rheumatoid arthritis

Abstract: Groups of 15 patients with active rheumatoid arthritis were treated for 24 weeks with zinc sulphate, trien, captopril, clozic in two doses or a combination of D-penicillamine and hydroxychloroquine. Serum histidine levels were monitored along with measures of disease activity including C-reactive protein, plasma viscosity, articular index, grip strength and early morning stiffness. Zinc sulphate and trien were found to be ineffective while the other drugs all showed evidence of second-line action. Serum histid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Second, we were unable to collect information regarding the types and doses of lipid-lowering drugs. Nevertheless, previous studies have reported that commonly used lipid-lowering drugs showed similar effects on KOA 33 – 35 . Third, we did not collect information regarding dietary patterns and were unable to evaluate the possible confounding influence of this factor.…”
Section: Discussionmentioning
confidence: 93%
“…Second, we were unable to collect information regarding the types and doses of lipid-lowering drugs. Nevertheless, previous studies have reported that commonly used lipid-lowering drugs showed similar effects on KOA 33 – 35 . Third, we did not collect information regarding dietary patterns and were unable to evaluate the possible confounding influence of this factor.…”
Section: Discussionmentioning
confidence: 93%
“…Reduced glycine and histidine in OA cartilage samples have been reported in metabolomics analyses using high-resolution nuclear magnetic resonance spectroscopy [ 14 16 ], and serum valine to histidine and leucine to histidine ratios have been proposed to be potential biomarkers for the management of OA [ 17 ]. In addition, reduced urinary glycine and histidine levels were also found to be associated with a poor response to methotrexate treatment in a collagen-induced arthritis animal model [ 18 ]. Taken together, evidence strongly suggests that glycine and histidine as well as their relevant metabolic pathways may undergo pathological alterations during the development of OA.…”
Section: Discussionmentioning
confidence: 99%
“…fibrate treatment in patients with RA, while in the study by Goto, fibrates had no effect [McConkey et al 1980;Goto, 2010]. Bird and colleagues demonstrated a significant reduction in CRP and ESR after treating patients with RA with 300 mg clofibrate, which was also shown by Dixon and colleagues for CRP [Bird et al 1983;Dixon et al 1983]. Reynolds and colleagues reported a nonsignificant reduction in CRP and ESR levels [Reynolds et al 1981].…”
Section: Reduction Of Systemic Inflammatory Parametersmentioning
confidence: 92%
“…Dixon and colleagues and Bird and colleagues reported a significant improvement in the articular index [Ritchie et al 1969] and early morning stiffness after treatment with 300 mg clobuzarit. This reduction was not seen with 100 mg clobuzarit [Bird et al 1983;Dixon et al 1983]. Bird and colleagues also showed a significant improvement in grip strength when 100 mg or 300 mg clobuzarit was given, which was not seen in the study by Dixon and colleagues [Bird et al 1983;Dixon et al 1983].…”
Section: Clinical Effectsmentioning
confidence: 97%
See 1 more Smart Citation